6(-3x+2)+12=(-210)

Simple and best practice solution for 6(-3x+2)+12=(-210) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-3x+2)+12=(-210) equation:


Simplifying
6(-3x + 2) + 12 = (-210)

Reorder the terms:
6(2 + -3x) + 12 = (-210)
(2 * 6 + -3x * 6) + 12 = (-210)
(12 + -18x) + 12 = (-210)

Reorder the terms:
12 + 12 + -18x = (-210)

Combine like terms: 12 + 12 = 24
24 + -18x = (-210)
24 + -18x = -210

Solving
24 + -18x = -210

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -18x = -210 + -24

Combine like terms: 24 + -24 = 0
0 + -18x = -210 + -24
-18x = -210 + -24

Combine like terms: -210 + -24 = -234
-18x = -234

Divide each side by '-18'.
x = 13

Simplifying
x = 13

See similar equations:

| n+7=2n-6 | | 5(8x+6)+12=402 | | 5(5+8r)= | | 2a=a+13 | | 2a=s+13 | | -142=-2-10x | | 3-(3-7)=43 | | 5-7y=h+7 | | x+30+x+20+x+10=180 | | 10(3+11g)= | | -3-7(3+2m)=-94 | | -0.6=0.3(k+2) | | 2x+4y+7-2z= | | 3m-2n=7m-7-4.8n | | 2x-10+2x=3(4x-6)+6 | | 2a=a+16 | | 7(5b+4)= | | 2X-3/15 | | m^2-28m=11 | | 2v-68=v | | E=7+5x | | 6+2x+9=24+32+6x+12 | | -7(10-10x)-8x= | | (3x+4)+(2x+2)=5(1x-1)+8 | | 2p-26=p | | 4(x-3)+18=3(x+3) | | 2x-3(x-5)=7 | | 6b-61=b+4 | | 6(3n-7)=84 | | 2x^4/5=25 | | x(x+2)=x(5+x) | | 10a+4(a+1)=32 |

Equations solver categories